Comparative study of combination of misoprostol with Foley’s bulb compared with misoprostol alone for termination of second trimester pregnancy - Agarwal, Priya; Gandhi, Sudha; Indora, Prachika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Second trimester abortion is termination of pregnancy in a period from 13 to 28 weeks of gestation. Second trimester losses may be due to maternal factors such as uterine malformation, growths in the uterus (fibroids), or cervical problems. These conditions also may contribute to premature birth. Aims and objectives were to compare the efficacy, safety and suitability of combination of misoprostol with intracervical Foley’s catheter v/s misoprostol alone for termination of second trimester pregnancy. Methods: This randomized controlled trial study was conducted on 100 study subjects who passed our inclusion and exclusion criteria. Group A: received misoprostol with intracervical Foley’s catheter. Group B: received misoprostol alone. The groups were compared with respect to the patients’ characteristics, gestational age, indication for termination of pregnancy, rate of complications, etc. Results: Mean value of age (years) of study subjects was 27.12±4.5. Mean induction to delivery time (hours) in P0 was 17.73±6.46 and in P1-P2 was 14.78±4.9 which was significantly higher as compared to ≥P3 (11.46±3.82). (p=0.0004). Mean induction to delivery time (hours) in 14 to 18 weeks was 15.25±5.4 and >18 weeks was 15.02±5.84. (p=0.854). Distribution of side effect between group A and B. (6% vs 20% respectively) (p=0.041). Conclusions: We conclude that intracervical Foley catheter and vaginal misoprostol is a safe and effective method for second trimester abortion as compared to misoprostol alone group with no additional risks.